FRI0158 Prostaglandin e2 and its receptor subtype ep4 are involved in ankylosing spondylitis disease progression. (12th June 2018) - Srinath, A.; Haroon, N.; Guggino, G.; Sari, I.; Zeng, F.; Alessandro, R.; Rizzo, A.; Ciccia, F.
Abstract : Background: Single Nucleotide Polymorphisms (SNPs) in PTGER4 were found to be associated with Ankylosing spondylitis (AS) in GWAS. PTGER4 codes for the prostaglandin-E2 receptor EP4. PGE2/EP4 interaction can affect bone formation and inflammation. Objectives: We studied serum PGE2 levels and SNPs in PTGER4 in relation to spinal fusion in AS patients. We also evaluated the interaction of smoking, PGE2 and EP4 in driving IL23 production and ILC3 functions. Methods: Patients diagnosed with AS using the modified New York criteria and followed prospectively using a standardised protocol, were included in this study. Biological samples including serum, gut, synovial and bone marrow (BM) samples, DNA and RNA were stored and radiographs of the spine obtained every two years to assess progression. ELISA for Serum PGE2 and immunohistochemistry tissue expression of PTGS1, EP4 and pCREB were performed. Radiographs were scored by mSASSS. Patients with an increase of ≥1 mSASSS unit/year on follow up were deemed progressors. Five PTGER4 SNPs, associated with AS or related diseases, call rate above 90%, MAF >0.1 and not in LD above 0.8, were studied. Immune cell subsets from PBMCs were analysed for surface expression of the EP4 receptor. Additionally, PBMCs were incubated with nicotin, PGE2, or EP4 agonist to evaluate changes in ILC3 percentages and to determine cytokine expression by flow cytometry and RT-PCR. Results: Serum PGE2 levels were significantly higher in AS progressors (n=88) than in non-progressors (n=101) (p<0.001). In multivariable regression analysis, there was significantly more progression in patients with higher baseline mSASSS (B=0.02; p=0.01) and serum PGE2 (B=0.001; p=0.002), but lower progression with longer TNF inhibitor use (B=-0.01; p=0.03). There was a trend towards higher progression with higher baseline ESR (B=0.012; p=0.08). 3). A total of 172 AS patients had DNA and X-ray data for analysis. Patients with CC genotype of PTGER4 SNP rs6896969 were significantly more likely to progress compared to AA/AC (OR: 2.45, 95% CI: 1.3 to 4.6; p=0.006). Progressors tended to more likely be homozygous for the major allele G of the rs4957341 SNP (OR 2.1; 25% CI; 0.98–4.35; p=0.058). Increased expression of EP4, PTGS1 and pCREB were observed in the gut, BM and synovial samples of AS patients. EP4 expression was upregulated in circulating AS monocytes and ILC3, especially smokers, and the percentage of EP4 + monocytes and ILC3 correlated with the BASDAI. Sorted EP4 + CD14 + cells showed a higher expression of CREB and IL-23 and in vitro stimulation of monocytes with PGE2 increased IL-23 expression, demonstrating the functional relevance of EP4 expression on monocytes. The expression of EP4 is dependent on the transcription factor AP-2a (TFAP-2a). In vitro stimulation of monocytes with nicotine induced a significant monocyte over-expression of EP4 and TFAP-2a. Finally, PGE2 stimulation of isolated PBMC from AS patients significantly expanded IL-23-producing ILC3. Conclusions: PGE2 and its receptor EP4 are significant players in AS driving both inflammation and spinal fusion. The complex interaction of smoking, prostaglandin pathway upregulation and IL-23 dependent innate immune activation can contribute to the pathogenesis of AS Disclosure of Interest: None declared